PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN ONLINE MAHASISWI UNIVERSITAS HALU OLEO - Patwayati Patwayati; Nofal Nur; Olivia Anindyta Mashud (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to determine the influence of Social Media Instagram Against Purchase Decision Management Online Student Halu Oleo University. The benefits of this research is to provide benefits theoretically can be useful as a contribution of thought to the world of education and is also expected to be a reference to further research and contribute thoughts, knowledge, images, and information will Influence Social Media Instagram Against Decision Purchase Online fashion products Student Management University Halu Oleo . The population in this study is a regular student class of 2015-2017 Department of Management Faculty of Economics, University of Halu Oleo. The data student active management majors we can see amounted to 708. The sample in this study was 88 female students using slovin method.The result of research stated that social media of instagram have a significant effect to online purchasing decision.